2013
DOI: 10.1089/jwh.2013.4400
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Reporting of Sex Differences in Phase III Medical Device Clinical Trials—How Are We Doing?

Abstract: Over the past decade, the scientific community has begun to recognize the importance of biological sex differences in disease pathology, diagnosis, prevention, and treatment; however, the practice of sex-specific analysis and reporting is not integrated as standard practice by either our federal health agencies or by major medical journals. Despite the reforms of 20 years ago and the general inclusion of women in drug clinical trials, we have yet to see data routinely analyzed and reported by sex. Major journa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
(1 reference statement)
0
8
0
Order By: Relevance
“…50 Not only women enrollment but also sex-specific reporting was shown to be inadequately low in cardiovascular clinical trials. 15,51 Despite the broad recognition that taking sex-based differences into account for the development of guidelines or for devices innovation is essential, [52][53][54] only 23% of cardiovascular clinical trials published in several journals in 2004 reported sex-specific results. 19 We also observed a low sex-specific reporting in the present studies with 6 of 23 studies only considering female sex as an important covariate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Not only women enrollment but also sex-specific reporting was shown to be inadequately low in cardiovascular clinical trials. 15,51 Despite the broad recognition that taking sex-based differences into account for the development of guidelines or for devices innovation is essential, [52][53][54] only 23% of cardiovascular clinical trials published in several journals in 2004 reported sex-specific results. 19 We also observed a low sex-specific reporting in the present studies with 6 of 23 studies only considering female sex as an important covariate.…”
Section: Discussionmentioning
confidence: 99%
“…Gathering sufficient data on women is challenging in cardiovascular trials, as they tend to be underrepresented, [11][12][13] particularly in devices or interventional trials, such as trials investigating implantable cardioverter defibrillators (ICDs) implantations or coronary angiographies. [14][15][16][17] Moreover, despite the recognition of the growing importance of sex-based differences in medicine, 18 the reporting of sex-specific analyses was found to be low in a large number of publications. 19,20 Whether studies investigating catheter ablation for AF also tend to enroll more men than women and to poorly report sex-specific results is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Since the publication of our 2009 study, other researchers have examined the inclusion of women and minorities as well as reporting by sex or race/ethnicity in specific fields (e.g., HIV, cardiology) 10,11 and in particular clinical trial types (e.g., phase III clinical trials), 12,13 finding similarly inadequate adherence to NIH policies. The purpose of this study was to repeat our evaluation of NIH-funded RCTs in a broad sample of high impact journals published in 2015 to determine whether rates of inclusion and reporting have changed since 2009, more than two decades since the passage of the NIH Revitalization Act.…”
mentioning
confidence: 99%
“…Several of the articles call for more comparison of research findings by sex, noting that, like race and ethnicity, sex differences in many domains are still widely understudied. [56][57][58][59][60] Regardless of actual representation of females in biomedical research, many health outcomes specific to them will remain unknown unless researchers prioritize exploring differences across sex assigned at birth, race, and ethnicity. In addition, sex is predominantly perceived as a binary biological construct and individuals born as intersex, or those with disorders of sexual development, have difficulties "fitting" into a male/female binary category.…”
Section: Plos Onementioning
confidence: 99%
“…Including intersex as a biological construct is important for health care since individuals' needs may not apply to either the male or female classification. [59] The literature indicates that this is also true for transgender individuals who have undergone gender affirming surgeries or who receive hormonal treatments as well. [61] We identified literature that explained underrepresentation of select minority populations due to issues in how race and ethnicity data are traditionally collected and reported.…”
Section: Plos Onementioning
confidence: 99%